Do early midlife work characteristics predict 20-year change in control beliefs? - Hartung, Johanna; Stahlhofen, Lena; Schilling, Oliver; Wahl, Hans-Werner; Hülür, Gizem (Psychology and aging, 2024)
Previous research showed the importance of control beliefs for many life outcomes. The present study examines associations between subjectively perceived work environment and objectively measured work activities at the beginning of midlife as a central developmental phase in the context of work, with control beliefs across the subsequent 20 years. We analyzed four-wave longitudinal data from N = 374 participants (born 1950-1952; Mage baseline = 44 years, SD = 1; 44% women) from the Interdisciplinary Longitudinal Study of Adult Development and Aging within a structural equation modeling framework. Over 20 years and overall, internal control beliefs were stable, while external control beliefs decreased. Individuals who reported higher task variety and better social integration at work at baseline also reported higher levels of control beliefs for positive life outcomes. In addition, higher social integration at work at baseline was related to lower levels of external control beliefs. Work characteristics at baseline were not associated with individual differences in change in control beliefs across the 20-year observational interval. In summary, our findings suggest that work experiences at the prime of job-related development around the midst of the fifth decade of life do not play a major role in subsequent control beliefs development across 20 years. However, investigations measuring control beliefs as well as work characteristics continuously over a long period of time are necessary to shed light on reciprocal influences between work and personality. (PsycInfo Database Record (c) 2024 APA, all rights reserved)